Inpanting Citra Biner Menggunakan Metode Modus Matrik - Sudaryanto, Aris (JHP17 (Jurnal Hasil Penelitian), 2018)
Image is one of important element of multimedia. Image also contain a lot of important data information. But sometime the data inside image is lost because of noise, damage, or something. Image Inpainting is the process of reconstructing or retouching part or whole of an damage or unwanted image. In this research, image inpainting process is done by using the modus of its image value. The data image consist of ten binary image with 10 x 10 pixel size. The error count by reducing the absolute value of the original with the absolute value of the inpainting process. The method we propose has a high accuracy, as evidenced by 0% of error, and 100% of matching between original data and inpainting result data. Keywords: Image Inpainting, Modus Matrix, Binary Image.